Analysis of the Economic Situation of Energy Companies in Central and Eastern Europe - Rakos, Monika; Szendrak, Janos; Erdey, Laszlo; Komives, Peter Miklos; Fenyves, Veronika (International Journal of Energy Economics and Policy, 2022)
Nowadays our everyday life is unimaginable without energy, because all the sectors are using different forms of energy. In our article we decided to analyse the following question: what is the current economic status and situation of the energy companies in Central and Eastern Europe? We prepared our primary research by the use of a standard fixed-effect panel regression model to analyse the capital structure of the energy industry companies. The capital structure regression gave similar results in terms of parameter sign, while the firm size, profitability (ROA) and liquidity ratio have significant coefficients in all cases from Poland, Czechia, Slovakia, Romania, and Hungary. Asset structure denoted the fixed assets over total assets. According to the estimates, larger companies have higher share of leverage and may have easier access to external financing sources. The profitability of the firms (captured by ROA) and leverage had a negative relationship, thus profitable firms were less likely to rely on external finance.